2021
DOI: 10.1111/tid.13742
|View full text |Cite
|
Sign up to set email alerts
|

Association between adenovirus infection and mortality outcome among pediatric patients after hematopoietic stem cell transplant

Abstract: Background Adenovirus can cause severe diseases in post‐hematopoietic stem cell transplant (HSCT) patients. Because these patients also have many other factors contributing to mortality, it remains controversial whether adenovirus infection itself contributes to increased mortality in these patients. Objective To determine if adenovirus infection contributes to mortality in pediatric post‐HSCT patients. Methods This retrospective cohort study was performed in post HSCT patients, aged 0–18 years old, admitted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…We identified six risk factors associated with mortality in patients with AdV disease after allogeneic HCT. Among them, viremia or disseminated disease, older patient age, and diagnosis within 100 days after HCT were consistently reported in previous studies 10,28,32 . Intermediate, high, or very high rDRI, HCT‐CI ≥3, and previous HCT have not previously been reported.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…We identified six risk factors associated with mortality in patients with AdV disease after allogeneic HCT. Among them, viremia or disseminated disease, older patient age, and diagnosis within 100 days after HCT were consistently reported in previous studies 10,28,32 . Intermediate, high, or very high rDRI, HCT‐CI ≥3, and previous HCT have not previously been reported.…”
Section: Discussionsupporting
confidence: 61%
“…Among them, viremia or disseminated disease, older patient age, and diagnosis within 100 days after HCT were consistently reported in previous studies. 10,28,32 Intermediate, high, or very high rDRI, HCT-CI ≥3, and previous HCT have not previously been reported. Our results showed that regardless of the infection burden, AdV disease was associated with an increased risk of mortality after both autologous and allogeneic HCT.…”
Section: Discussionmentioning
confidence: 91%
“…30 In another study on 125 HCT pediatric patients, the presence of AdV viremia, AdV viral load ≥ 10 4 copies/mL, and endorgan diseases were associated with mortality. 31 Duration and entity of AdV replication have an impact on the patient outcome. In a retrospective analysis of 241 pediatric HCT patients with AdV infection, both a higher peak level and duration of AdV viremia ≥ 10 3 copies/mL were independent risk factors for the 6-month probability of mortality.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In a prospective study of 238 pediatric HCT, an AdV viral load ≥ 10 4 copies/mL in the blood resulted in an independent risk factor for poor survival 30 . In another study on 125 HCT pediatric patients, the presence of AdV viremia, AdV viral load ≥ 10 4 copies/mL, and end‐organ diseases were associated with mortality 31 . Duration and entity of AdV replication have an impact on the patient outcome.…”
Section: Risk Factorsmentioning
confidence: 99%
“…However, the impact of viral infectious complications on outcome is recognized to be as significant in adults as in pediatric allo-HSCT recipients. 5 In fact, in the case of ADV viremia (ADVv), the reported mortality rate was up to 73% in adults 6 and 82% in children, [7][8][9] and in more recent series 30% 10 and 25%, [11][12][13][14] respectively.…”
Section: Introductionmentioning
confidence: 99%